Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1158/1535-7163.mct-18-1167
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestins Regulate Stem Cell-Like Phenotype and Response to Chemotherapy in Bladder Cancer

Abstract: b-Arrestins are classic attenuators of G-protein-coupled receptor signaling. However, they have multiple roles in cellular physiology, including carcinogenesis. This work shows for the first time that b-arrestins have prognostic significance for predicting metastasis and response to chemotherapy in bladder cancer. b-Arrestin-1 (ARRB1) and b-arrestin-2 (ARRB2) mRNA levels were measured by quantitative RT-PCR in two clinical specimen cohorts (n ¼ 63 and 43). The role of ARRBs in regulating a stem cell-like pheno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…Arrestin beta 1 (ARRB1) is one of the beta arrestins regulating various cellular physiologic processes, and have been demonstrated to have pro-tumorigenic effects [35,36]. Kallifatidis et al recently reported increased ARRB1 expression in bladder cancer cells, and ARRB1 gene knockout reversed the aggressive phenotype of bladder cancer cell lines [37]. MiR-185-3p is a potential oncosuppressor miRNA evident in nasopharyngeal carcinoma (NPC), and the inhibition of miR-185-3p promoted invasion and metastasis of NPC cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Arrestin beta 1 (ARRB1) is one of the beta arrestins regulating various cellular physiologic processes, and have been demonstrated to have pro-tumorigenic effects [35,36]. Kallifatidis et al recently reported increased ARRB1 expression in bladder cancer cells, and ARRB1 gene knockout reversed the aggressive phenotype of bladder cancer cell lines [37]. MiR-185-3p is a potential oncosuppressor miRNA evident in nasopharyngeal carcinoma (NPC), and the inhibition of miR-185-3p promoted invasion and metastasis of NPC cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…ARRB1 knock out cells were generated by CRISPR/Cas9 genome editing technology and evaluated as described in our previous work [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, in certain circumstances, β-arrestins can function as adaptor molecules that mediate G-protein independent signaling by serving as scaffolds that link signaling networks [ 18 ]. Our previous work shows that β-arrestins regulate stem cell properties in BC [ 19 ]. We have demonstrated that ARRB1 regulates the CSC markers CD44 and Bmi1 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins specific to immune privileged zones, such as cancer-retina antigens, were shown to be aberrantly expressed in malignant tumors ( Golovastova et al, 2014 ). Among these proteins, recoverin ( Golovastova et al, 2016 ) and arrestin ( Baldin et al, 2019 ; Kallifatidis et al, 2019 ) were found to be highly predictive biomarkers of renal cell carcinoma and BC. However, they have never been considered as low-invasive blood or urine biomarkers.…”
Section: Introductionmentioning
confidence: 99%